Are Social Networking Sites (SNS) effective platforms for political engagement? - Leon van Jaarsveldt (International Telecommunications Society (ITS), 2011)
Based on a dataset by Pew Internet and American life project on the 2008 Post election results in the United States, this research aims to determine whether the frequency of SNS usage, the amount of SNS profiles, the number of SNS platforms and the use of SNS platforms for political purposes, especially through the 'friend' function, positively predict online political engagement and online political information seeking. The findings show that while the number of SNS profiles have no impact on either dependent variable, the number of SNS platforms plays a role in online political engagement while the frequency of use plays a strong role in both online political engagement and online political information seeking. The findings also indicate a strong relationship between using SNSs for political purposes, especially for finding campaign or candidate information on the site and for learning friends' political interests or affiliation, and online political engagement and online political information seeking, as well as for starting or joining a cause and becoming a 'friend' of a political candidate.
Keywords: 330